According to the Revolutionary of Tasawwuf Shah Walilullah dehlawi In the Indian Sub-continent - คอนัม ดารดานะห์ (Al-HIKMAH Journal, 2018)
The purpose of this study is to throw the light on the idea of Tasawwuf (the path of Sufis or Sufism) according to the revolutionary and legendary Shah Walilullah Dehlawi (Rahimahu Allah) and its deep impact on the Muslim community across South Asian region. Though the very idea of Sufism was there a thousand years ago in some form or the other but Shah Waliullah, with his enlightened approach, made drastic changes in terms of how people perceive and practice Sufism. He was of the view that Sufism is not a new concept per se but the same old way of Al Qur’an and Prophet Mohammad (PBUH) which is vibrant, practical and completely void of extremes and malpractices. Shah Walilullah with his vision and knowledge was successful in transforming the Muslim society in South Asia (especially in India, Pakistan and Bangladesh) and he left the imprint of his thoughts which is visible even 250 years after his demise.